Peranan Sistem Pengamanan File Dan Cyber Security Terhadap Obyek Vital Pada PT Bank Central Asia (BCA) - Edy Soesanto; Nova Astia Ningsih; Muhammad Ilham Faturrahman; Lili Khoerunisa (Jurnal Akuntan Publik, 2023)
Along with the rapid development of information technology, customer interaction with BCA digitally has also increased. This is followed by the risk of technology crime, so BCA continues to improve its information technology security system. The development of BCA's data security system is carried out with the aim of protecting data security and ensuring information technology systems are always ready to serve customer transactions, including preventing and anticipating cybercrimes and potential fraud. National vital objects have an important role in the life of the nation and state, both in terms of economic, political, social, cultural, defense, and security aspects. National vital objects also have a quite strategic role in national development. Data Loss Prevention (DLP) is a data security strategy implemented by BCA on an ongoing basis to increase the security of important electronic information from information theft or access by unauthorized parties. To ensure security in accessing BCA's internal applications that are connected to the internet, BCA applies additional security in the form of two-factor authentication to ensure access to the application is carried out by the right person. BCA has also used a data classification solution to ensure that every piece of data in the company is classified according to the level of data confidentiality.